Environmental incentives of entrepreneurship: Fuzzy clustering approach to OECD countries - Anıl Boz Semerci; Mustafa Çimen (Journal of Global Entrepreneurship Research, 2017)
The rate of nascent entrepreneurship is crucial for economies of countries in order to identify economic well-being and promote dynamics for new business start-ups. Supportive governmental programs, proper entrepreneurship education and predisposition of cultural and social norms are encouraging factors that assist new businesses and develop entrepreneurial and innovative structures in economies. This research classifies countries and examines the clusters according to their governmental supportive programs, educational incentives, cultural and social norms on entrepreneurship and the rate of new entries into self-employment in the country. For the analyses, fuzzy clustering method is applied on the entrepreneurship key indicators data, obtained from the Global Entrepreneurship Monitor (GEM) study. Although our analyses do not allow the identification of causal relationships, they provide useful comparisons among the countries and suggest incentive mechanisms for policy makers according to their clusters. Given the importance of entrepreneurship and new business ventures, the findings of this study form an important base for further empirical studies, in addition to its practical value on public, educational and social point of views in entrepreneurship.
Keywords: 650; Entrepreneurship; Nascent entrepreneur; Governmental programs; Education; Culture and social norms